Enhanced nicotine-seeking behavior following pre-exposure to repeated cocaine is accompanied by changes in BDNF in the nucleus accumbens of rats - Leão, Rodrigo M. [UNESP]; Cruz, Fábio C. [UNESP]; Carneiro-De-Oliveira, Paulo E. [UNESP]; Rossetto, Daniella B. [UNESP]; Valentini, Sandro Roberto [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Planeta, Cleopatra da Silva [UNESP] (Elsevier, 2013)
We investigated the behavioral and molecular interactions between cocaine and nicotine, through evaluating locomotor activity, nicotine intravenous self-administration and gene expression. Locomotor sensitization was induced in male Wistar rats by repeated cocaine (20 mg/kg; i.p.) or saline injections once a day over 7 days. Three days after the last injection, rats were challenged with either saline or cocaine (15 mg/kg; i.p.) and the locomotor activity was measured. The very next day animals received either saline or nicotine (0.4 mg/kg; s.c.) and the locomotor cross-sensitization was tested. Animals were then prepared with intrajugular catheters for nicotine self-administration. Nicotine self-administration patterns were evaluated using fixed or progressive ratio schedules of reinforcement and a 24-h unlimited access binge. Immediately after the binge sessions animals were decapitated, the brains were removed and the nucleus accumbens was dissected. The dynorphin (DYN), μ-opioid receptor (mu opioid), neuropeptide Y (NPY), brain-derived neurotrophic factor (BDNF), tropomyosin-related tyrosine kinase B receptor (TrkB) and corticotropin- releasing factor receptor type 1 (CRF-R1) gene expression were measured by the reverse transcription-polymerase chain reaction (RT-PCR). Pretreatment with cocaine caused sensitization of cocaine motor response and locomotor cross-sensitization with nicotine. In the self-administration experiments repeated cocaine administration caused an increase in the nicotine break point and nicotine intake during a 24 h binge session. © 2013 Elsevier Inc.
Keywords: BDNF; Cocaine; Gene expression; Locomotor activity; Nicotine; RT-PCR; Self-administration; brain derived neurotrophic factor; brain derived neurotrophic factor receptor; cocaine; corticotropin releasing factor; dynorphin; mu opiate receptor; nicotine; sodium chloride; animal experiment; animal model; animal tissue; brain tissue; controlled study; cross allergy; decapitation; drug seeking behavior; gene expression; locomotion; male; nonhuman; nucleus accumbens; priority journal; rat; reinforcement; reverse transcription polymerase chain reaction; Animals; Brain-Derived Neurotrophic Factor; Dynorphins; Gene Expression; Male; Motor Activity; Neuropeptide Y; Nucleus Accumbens; Rats; Rats, Wistar; Receptor, trkB; Receptors, Corticotropin-Releasing Hormone; Receptors, Opioid, mu; Risk Factors; Self Administration; Tobacco Use Disorder; Animalia; Rattus; Rattus norvegicus